Analysis of Learning Problems in Chemistry at Eria Medan Private High School - Rafika Utami (Research Center for Chemistry - LIPI, 2018)
AbstractThe purpose of this study was to determine the learning process and to analyze the problem of learning chemistry in senior high school. The approach used in this study was a qualitative approach. This mini research was conducted at Eria Medan Private Senior High School in 2017. Research subjects were selected by purposive sampling of 35 Mathematic and Natural Science 1, students grade XI. Data were collected and recorded using observation sheet to measure teacher activities. Students responses were obtained using a questionnaire. The result identified some problems that may inhibit the learning process. Only 37,14 % students were happy to complete or practice with questions and 42.85% of students are actively involved in the learning process. In addition, 80% of students stated that the chemistry books used were less interesting and only 20% of students stated their chemistry book was interesting to read.This study also found that there are misconceptions in teaching concept in the subject of chemical equilibrium.